The effectiveness of compassion therapy on blood sugar, happiness and death anxiety in the elderly with type 2 diabetes - Sarmadi, Maryam; Safarinia, Majid; Tizdast, Taher; Nejat, Hamid (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was conducted with the aim of determining the effectiveness of compassion therapy on blood sugar, happiness and death anxiety of the elderly with type 2 diabetes. Method: This was a semi-experimental research with a pre-test and post-test design with a control group and a follow-up period. Among the elderly women with diabetes in the 1st district of Tehran in the year 2021, 29 people were selected as available research samples according to the study entry criteria and randomly replaced in two experimental and control groups. The tools used in this research included blood tests, Oxford happiness questionnaire (2001) and Templer's death anxiety (1970). Data were analyzed by repeated-measures analysis of variance. Results: The results showed that there was a significant difference between the mean of the pre-test and the follow-up test of the experimental and control groups in terms of blood sugar, happiness and death anxiety. In other words, compassion therapy reduced blood sugar and death anxiety and increased happiness in the elderly with type 2 diabetes (p